Critical Analysis of Michael J. Sandal’s Philosophy of Political and Social Affairs - Ahmad Reza Tabatabai (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Michael J. Sandal (born March 1993) is an American Political philosopher and professor at Harward University. He is best known for the Harward Course Justice and for his critique of John Rawls’s “Theory of Justice”. Sandal in his book "Public Philosophy", which is about his ideas in "Morality in Politics" has explained his philosophical and Political thoughts with real and objective examples. In this book, he has tried to lead abstract philosophical discussions into concrete political and social affairs. The author has tried to explain the relationship between ethics and politics in American society with concrete examples. The author of the present article aims to clarify Saddle’s view in ethics and politics as well as his critical thoughts about Rawls’s Theory of Justice.